Sensitivity of Gravity‐Wave Momentum Flux to Moisture in the Mei‐Yu Front Systems. Issue 13 (8th July 2019) - Wang, Yuan; Zhang, Lifeng; Zhang, Yun; Peng, Jun; Yu, Shiwang
Abstract: The sensitivity of gravity‐wave momentum flux in the Mei‐Yu front systems to moisture is investigated via idealized simulations with various degrees of initial moisture content. Gravity waves generated in moist experiments result in net northward momentum flux and drag forcing, and the drag is indistinctive in the lower stratosphere near the tropopause but strengthens with height. As moisture content increases, the meridional flux intensifies remarkably in both physical and spectral space and extends to smaller spatiotemporal scales. However, the change of moisture has little effect on the selectivity of the strongest flux to relatively large scales and specific phase speeds. At slow phase speeds, the fanlike waves excited by the front are effectively coupled with the convective waves excited by the prefrontal moist convection, which leads to the weakening of the coupled wave flux. Plain Language Summary: Differing from the typical midlatitude polar front, the Mei‐Yu front in the East Asian monsoon region is characterized by a weak temperature gradient but strong moisture gradient and persistent precipitation and is strongly affected by moisture and diabatic heating. A previous study showed that gravity waves generated in the Mei‐Yu front are distinct from those generated in a traditional dry front due to the moisture and resulting moist convection. In this study, by performing sensitivity experiments, we further investigate the detailed effects of varying moisture content on momentum flux induced by gravity waves in the Mei‐Yu front systems. It is found that gravity waves in the systems induce net northward momentum flux and drag forcing. The drag on the background flow is indistinctive in the lower stratosphere but strengthens with height, and the influence of moisture on the drag also increases with height. The increase of moisture in general intensifies the momentum flux, but the strongest flux is still found at relatively large scales and specific phase speeds. The fanlike waves excited by the front are strongly coupled with the convective wave excited by the prefrontal convection at slow phase speeds, which leads to the weakening of local wave flux. Key Points: Drag forcing of gravity waves on background flow strengths with height and the influence of moisture on the drag also increases with height The increase of moisture intensifies the momentum flux but barely modifies the selectivity of strongest flux to specific scales The fanlike waves are coupled with the convective waves at slow phase speeds, which results in a weakening of local wave flux